Annotated catalog of the northwest Caucasian Nepomorpha and Gerromorpha (Heteroptera) - Shapovalov, Maksim I.; Saprykin, Maksim A.; Prokin, Alexandr A. (Zootaxa, 2018)
A catalog of aquatic and semiaquatic Heteroptera of the northwest Caucasus is provided based on literature reports and field collections. Representatives of 50 species of the infraorders Nepomorpha and Gerromorpha are listed and are distributed in 11 families, including Aphelocheiridae (1 genus, 1 species), Corixidae (6 genera, 23 species), Gerridae (3 genera, 9 species), Hebridae (1 genus, 2 species), Hydrometridae (1 genus, 2 species), Mesoveliidae (1 genus, 1 species), Naucoridae (1 genus, 1 species), Nepidae (2 genera, 3 species), Notonectidae (2 genera, 4 species), Pleidae (1 genus, 1 species) and Veliidae (2 genera, 3 species). Five species listed for the fauna of the northwest Caucasus are doubtful. Types of ranges of all species are given. Zoogeography of the regional fauna is discussed.